Optimasi Pemurnian Minyak Jelantah Menggunakan Lempung Teraktivasi Asam Klorida melalui Variasi Waktu Kontak dan Dosis - Fransiska Yuliati; Kartini Rahman Nisa; Kristina Teresia Leto (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to optimize the purification of waste cooking oil using hydrochloric acid (HCl)-activated clay as an adsorbent. Repeated use of cooking oil causes chemical degradation, leading to an increase in free fatty acids and the formation of harmful compounds that pose health risks. Therefore, an effective and economical purification method is required. This research employed a factorial experimental design by varying contact time (20, 40, and 60 minutes) and adsorbent dosage (1, 2, and 3 grams). The effectiveness of the treatment was evaluated based on acid number, color, and odor, and the data were analyzed descriptively. The results showed that activated clay significantly improved the physical characteristics of the oil by reducing unpleasant odor and increasing clarity. The lowest acid number based on contact time was obtained at 40 minutes (2.8 mg NaOH/g), while the optimum adsorbent dosage was 2 grams (1.6 mg NaOH/g). However, the resulting acid values have not yet met the Indonesian National Standard (SNI). These findings indicate that HCl-activated clay has strong potential as a low-cost adsorbent for waste cooking oil purification, although further optimization is required to meet quality standards.